Self-Presentation Komunitas Indonesian Subculture Melawan Stigma Kriminalitas - Ronald Yehezkiel Jasita; Gregorius Genep Sukendro (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
In Indonesia, there are still many assumptions that people with tattoos are synonymous with criminal behavior. Seeing the stigma of criminality against tattoos in society, this is the beginning of the formation of the Indonesian Subculture community. Indonesian Subculture is one of the tattoo communities in Jakarta that has been formed since July 9, 2004. This community is slowly changing its assessment of people with tattoos. This is related to the self-presentation displayed by Indonesian Subculture in the community in fighting the stigma of tattooing as one of the characteristics of a criminal in society. Therefore, the authors are interested in conducting research with a qualitative approach and case study research methods. The purpose of this study is to determine the self-presentations presented by Indonesian Subculture in an effort to fight the stigma of crime in society. The data analyzed were the result of interviews, direct observation, and documentation. The results showed that the self-presentation shown by Indonesian Subculture in fighting the stigma of crime in society was to form a positive community concept through the slogan and vision and mission, namely always having safe and healthy tattoos / piercing, holding various positive activities. These activities include a coaching clinic, social service, tattoo and piercing competitions, as well as tattoo / piercing educational activities.Di Indonesia, masih banyak anggapan orang bertato identik dengan perilaku tindak kriminal. Melihat adanya stigma kriminalitas terhadap tattoo di masyarakat, menjadi awal mula terbentuknya komunitas Indonesian Subculture. Indonesian Subculture merupakan salah satu komunitas tattoo di Jakarta yang telah dibentuk sejak 9 Juli 2004. Komunitas ini perlahan mengubah penilaian terhadap orang bertato. Hal ini berkaitan dengan self-presentation yang ditampilkan Indonesian Subculture di masyarakat dalam melawan stigma tattoo sebagai salah satu ciri seorang pelaku tindak kriminalitas di masyarakat. Oleh karena itu, penulis tertarik untuk melakukan penelitian dengan pendekatan kualitatif dan metode penelitian studi kasus. Adapun tujuan dari penelitian ini adalah untuk mengetahui self-presentation yang ditampilkan Indonesian Subculture dalam upaya melawan stigma kriminalitas di masyarakat. Data yang dianalisis merupakan hasil wawancara, pengamatan langsung, serta dokumentasi. Hasil penelitian menunjukkan bahwa self-presentation yang ditunjukan Indonesian Subculture dalam melawan stigma kriminalitas di masyarakat adalah membentuk konsep komunitas yang positif melalui slogan dan visi misi yakni selalu bertato/piercing yang aman dan sehat, menyelenggarakan berbagai kegiatan-kegiatan positif. Kegiatan tersebut antara lain coaching clinic, bakti sosial, lomba tattoo dan piercing, serta kegiatan edukasi bertato/piercing.